ECONOMICAL SCHEME-TECHNICAL SOLUTIONS IN AUTOMATION SYSTEMS OF AGRARIAN PRODUCTION - Vladimir V. Rusanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article analyzes systems of agro-technical production automation by using scheme-technical solutions based on integral micro-schemes of high degree of integration, universal micro-controllers and micro-controlling platform ARDUINO with the open code for programming. A concrete task was chosen for the analysis, i.e. providing comfort conditions in open-air cages for raising sucking pigs in the initial period of their life. The author shows methods of using devices to measure climatic parameters and commutation equipment in order to switch on executive devices of the automatic control system. As a result of testing all solutions being discussed it was found out that in case of mass production of the control system of the same type it is expedient to use universal micro-controller and the control program for it will be designed and adjusted.